Examination of the “susceptibility gap” in the treatment of canine heartworm infection - Dwight D. Bowman; Jason Drake (Parasites & Vectors, 2017)
Abstract Background The “susceptibility gap” in a dog diagnosed with adult heartworms has been defined as the period of time in which some Dirofilaria immitis stages are not susceptible to treatment with either macrocyclic lactones or melarsomine dihydrochloride. This was previously defined within the American Heartworm Society guidelines as a period of about 3 months “as per product labels.” It can be postulated, however, that a susceptibility gap does not exist with the combination of continued macrocyclic lactone therapy coupled with a three-dose melarsomine dihydrochloride protocol where the first intramuscular treatment is near the time of first diagnosis. Discussion Melarsomine dihydrochloride was originally also investigated as a “preventive” as well as a treatment for adult heartworm infection where it would be given to dogs by intramuscular injection every 4 months; therefore, there was early interest in its ability to kill younger worms. A single intramuscular injection of 2.5 mg melarsomine dihydrochloride/kg has an efficacy of 82.1% against 4-month-old worms. When it was given to dogs with older heartworms, 7 and 12 months of age, a single injection was only 55.6% and 51.7% effective, respectively. Thiacetarsamide has been shown to be 99.7% effective against 2-month-old heartworms and other work has shown that melarsomine dihydrochloride is 100% efficacious against these younger forms. With the development and US Food and Drug Administration (FDA) approval of spinosad + milbemycin oxime (Trifexis®, Elanco), milbemycin oxime + praziquantel (Interceptor® Plus, Novartis, now Elanco), and milbemycin oxime + lufenuron + praziquantel (Sentinel® Spectrum®, Novartis, now Virbac), it was shown that repeated treatments of dogs with milbemycin oxime also has efficacy against 3-month-old heartworms. Thus, no improvement in efficacy is expected with a delay in initiating therapy with both melarsomine dihydrochloride and macrocyclic lactones, even with the presence of younger heartworms. Starting treatment at diagnosis appears to be acceptable for maximal heartworm clearance based on published data. Delaying treatment has the disadvantage of allowing disease progression and continued heartworm growth. Conclusions The collective data that has been reviewed indicates that continued macrocyclic lactone administration with two additional injections of melarsomine dihydrochloride a month later will protect dogs against all heartworm stages, including those heartworms 2 months of age or younger at diagnosis, when both treatments are started upon diagnosis.